2015
DOI: 10.1515/ijsl-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Failure to launch: matching language policy with literacy accomplishment in South African schools

Abstract: This article argues that the education crisis in South Africa stems largely from a literacy problem. The prediction that use of the primary language is beneficial in formal schooling is not unambiguously met in the South African context when examining evidence from large-scale literacy assessments. Understanding the reasons for this is critical for improving the use of African languages in early schooling. This article examines the Zulu and English reading literacy skills of a Grade 4 cohort of learners after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…The very poor comprehension levels in both the HL and in English FAL, even in terms of literal understanding, suggest that teachers are not effectively developing learners' basic reading skills that support comprehension. Research into the relationship between decoding and comprehension skills in both the HL and FAL suggests that many learners struggle even to decode the texts that they read (Pretorius, 2012;Van Rooy & Pretorius, 2013;Pretorius, 2015). So even if South African teachers are spending more instructional time on decoding rather than on comprehension, it is not being done effectively.…”
Section: Focus Of Instructional Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very poor comprehension levels in both the HL and in English FAL, even in terms of literal understanding, suggest that teachers are not effectively developing learners' basic reading skills that support comprehension. Research into the relationship between decoding and comprehension skills in both the HL and FAL suggests that many learners struggle even to decode the texts that they read (Pretorius, 2012;Van Rooy & Pretorius, 2013;Pretorius, 2015). So even if South African teachers are spending more instructional time on decoding rather than on comprehension, it is not being done effectively.…”
Section: Focus Of Instructional Attentionmentioning
confidence: 99%
“…South African classroom research has consistently shown a lack of writing activities undertaken in low performing schools (Howie et al, 2008;Zimmerman & Smit, 2014;Pretorius, 2015). The recent introduction by the Department of Basic Education of colourful workbooks at all grade levels in all languages may account for the high incidence now of comprehension activities in workbooks, especially in Quintile 1-3 schools.…”
Section: Figure 8: Common Post-reading Activitiesmentioning
confidence: 99%
“…attention to language is one of the most important acts that can be done to improve the quality of science education" (2001, p. 1). Proficiency in LOLT, usually English, is one of the major obstacles to progress in the South African low-quintile context (Pretorius, 2015). Vocabulary acquisition, the first step towards language competence, requires repetition (Chukharev-Hudilainen & Klepikova, 2016), suggesting that drill-and-practise worksheets and software are appropriate ways to support the acquisition of the vocabulary foundational to the learning of science concepts.…”
Section: Low-language-demand Drill-and-practise Resourcesmentioning
confidence: 99%
“…Obstacles to progress in the context of learners learning the sciences in low-quintile South African schools include a poor command of the language of learning and teaching (LOLT) (Pretorius, 2015); low levels of prior knowledge and skill of learners and teachers; a general attitude of apathy; and inefficient use of time (Van der Berg, Spaull, Wills, Gustafsson, & Kotzé, 2016). This article contributes to the search for possibilities which may be implementable in the South African low-quintile school context given these problems, and possible amelioration of them.…”
Section: Introductionmentioning
confidence: 99%
“…The early literacy skills required to become a reader and writer were limited because of the focus on oral language development and the lack of access to printed materials. According to Pretorius (2015), oral language proficiency is a necessary but not sufficient condition to learning to read and write in a language, whether it is the child's L1 or L2. Children must be explicitly taught to read and write and given ample opportunities to practice literacy skills in extended texts and writing activities in order to become skilled readers and writers.…”
Section: Instructional Practices To Develop Reading and Writing Skillsmentioning
confidence: 99%